Habituasi Penulisan Karya Ilmiah Populer bagi Guru Pesantren Wilayah Cirebon - Pradi Khusufi Syamsu; Ade Hidayat (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
POPULAR SCIENTIFIC ARTICLE WRITING HABITUATION FOR ISLAMIC BOARDING SCHOOL TEACHERS IN THE CIREBON REGION. This community service activity aims to provide education to Islamic boarding school teachers about writing popular scientific papers, techniques for writing popular scientific papers and improving the ability of Islamic boarding school teachers to compose and publish popular scientific papers. The methods used are lecture, discussion, mentoring, monitoring, and evaluation methods. The material presented is an explanation of popular scientific works, techniques for writing popular scientific works, and the preparation of popular scientific works. The results obtained from this activity are an increase in the knowledge and skills of Islamic boarding school teachers in writing popular scientific articles, which is proven in the form of book publications. This activity concluded that the training in writing popular scientific works provided education for the training participants consisting of Islamic boarding school teachers in the Cirebon area about popular scientific works and techniques for preparing popular scientific works, as well as the practice of writing popular scientific works published in a book.